Effect of Bone Morphogenetic Protein–2 Combined With Microfracture for Osteochondral Defect of the Talus in a Rabbit Model. Issue 6 (May 2023) - Dang, Le Hoang Nam; Tran, Nhat Tien; Oh, Jong-Sung; Kwon, Tae-Young; Lee, Kwang-Bok
Background: Osteochondral defects of the talus can be effectively treated using microfracture, which is technically safe, accessible, and affordable. However, fibrous tissue and fibrocartilage comprise the majority of tissue repairs resulting from these procedures. These tissue types lack the mechanical characteristics of native hyaline cartilage and might significantly contribute to the decline in long-term outcomes. Recombinant human-bone morphogenetic protein–2 (rhBMP-2) has been shown to promote matrix synthesis and increase cartilage formation, thus enhancing chondrogenesis in vitro. Purpose: This study aimed to evaluate the treatment ability of combining rhBMP-2 with microfracture in rabbit talus osteochondral defect. Study Design: Controlled laboratory study. Methods: A full-thickness chondral defect (3 × 3 × 2 mm) was constructed in the center talar dome of 24 New Zealand White male rabbits, which were then divided into 4 groups of 6. Each group received the appropriate treatment: group 1 (control; no treatment of defect), group 2 (microfracture treatment), group 3 (rhBMP-2/hydroxyapatite treatment), and group 4 (microfracture combined with rhBMP-2/hydroxyapatite treatment). Animals were sacrificed at 2, 4, and 6 weeks postoperatively. The International Cartilage Regeneration & Joint Preservation Society macroscopic score, which considers the degree of defect repair, the integration to the border zone, and the macroscopic appearance, was used to assess the repaired tissue's macroscopic appearance. Subchondral bone regeneration in defects was analyzed using micro–computed tomography, and the histological findings were graded using a modified version of the Wakitani scoring system for osteochondral repair. Results: At 2, 4, and 6 weeks, micro-computed tomography analysis revealed that groups 3 and 4 exhibited subchondral bone healing that was more significantly improved compared with groups 1. No sample showed excessive bone growth from the subchondral bone area. According to macroscopic and histological results, group 4 showed higher-quality cartilage and more accelerated cartilage regeneration than the other groups over time. Conclusion: These findings show that osteochondral defect repair in a rabbit talus model could be effectively accelerated and improved by combining rhBMP-2 with microfracture. Clinical Relevance: Using rhBMP-2 in combination with microfracture may enhance the repair of talar osteochondral lesions.